Student Competencies: Hard Skills and Soft Skills Their Influence on Students' Job Readiness - Rina Fadilah; Kustini Kustini (LP2M IAIN Palopo, 2025)
This study aims to determine the influence of hard skills and soft skills on student job readiness at a private economics and business faculty in Surabaya. This research is a quantitative descriptive study. The subjects were students who were active in organizations and had participated in internship programs. The sample size was 60 students (Class of 2021). Purposive sampling was used because the subjects had certain characteristics that matched the research objectives. Based on these criteria, the study respondents consisted of 37 students majoring in management and 23 students majoring in accounting. Data analysis was performed using the partial least squares (PLS) method. The results showed that hard skills and soft skills have a positive and significant influence on student job readiness.